Evolutionary Recycling of Light Signaling Components in Fleshy Fruits: New Insights on the Role of Pigments to Monitor Ripening - Llorente, Briardo; D’Andrea, Lucio; Rodríguez-Concepción, Manuel (Frontiers in Plant Science, 2016)
Besides an essential source of energy, light provides environmental information to plants. Photosensory pathways are thought to have occurred early in plant evolution, probably at the time of the Archaeplastida ancestor, or perhaps even earlier. Manipulation of individual components of light perception and signaling networks in tomato (Solanum lycopersicum) affects the metabolism of ripening fruit at several levels. Most strikingly, recent experiments have shown that some of the molecular mechanisms originally devoted to sense and respond to environmental light cues have been re-adapted during evolution to provide plants with useful information on fruit ripening progression. In particular, the presence of chlorophylls in green fruit can strongly influence the spectral composition of the light filtered through the fruit pericarp. The concomitant changes in light quality can be perceived and transduced by phytochromes and phytochrome-interacting factors, respectively, to regulate gene expression and in turn modulate the production of carotenoids, a family of metabolites that are relevant for the final pigmentation of ripe fruits. We raise the hypothesis that the evolutionary recycling of light-signaling components to finely adjust pigmentation to the actual ripening stage of the fruit may have represented a selective advantage for primeval fleshy-fruited plants even before the extinction of dinosaurs.